Analýza prutových soustav s využitím principu tensegrity - Marek, Martin (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2024)
Tato bakalářská práce se zabývá prutovými soustavami s využitím speciálního principu tensegrity. Nastiňuje teoretický úvod do prutových soustav s vysvětlením základních podmínek existence těchto soustav. Dále popisuje základní teorii prutových soustav s využitím principu tensegrity, jejich charakteristiky, výhody a nevýhody. V rešeršní části pokračuje využití takzvané biotensegrity v přírodě a anatomii lidského těla, kterou následuje využití tensegrity v praxi. Po rešeršní části následuje výpočetní část, která obsahuje základní úvahy 2D úlohy jako jsou uvažované materiály a geometrie soustavy. Poté je popsán numerický výpočet v programu ANSYS a analytický výpočet v programu MATLAB. Jako poslední je popsán numerický výpočet 3D prutové konstrukce s využitím principu tensegrity.

This bachelor thesis focuses on strut frame structures using the tensegrity principle. It outlines a theoretical introduction to strut frame structures with an explanation of basic conditions of strut frame structure existence. It further describes the basic theory of strut frame structures using the tensegrity principle, their characteristics and their advantages and disadvantages. In the research section the occurence of biotensegrity in nature and human anatomy is presented. A description of use of tensegrity in practice is also presented. After the research section a computational section follows, this section contains basic thoughts used in the 2D model such as the considered materials and the strut frame geometry. A numerical computation in the ANSYS simulation software and an anlytical computation in MATLAB is presented. Last, a numerical computation of a 3D strut frame model with the tensegrity principle is described.
Analysis of strut frames structure using the tensegrity principle
Keywords: Prutové soustavy; Tensegrita; Předpětí; Lana; MATLAB; ANSYS; Strut frames; Tensegrity; Prestress; Ropes; MATLAB; ANSYS